Chaotic features of energy spectrum in 68Ge Nucleus Using the Nuclear Shell Model - Abd ALabas, Hayder Ali; Hamoudi, Adel Khalaf (Iraqi Journal of Physics, 2020)
Chaotic features of nuclear energy spectrum in 68Ge nucleus are investigated by nuclear shell model. The energies are calculated through doing shell model calculations employing the OXBASH computer code with effective interaction of F5PVH. The 68Ge nucleus is supposed to have an inert core of 56Ni with 12 nucleons (4 protons and 8 neutrons) move in the f5p-model space ( and ). The nuclear level density of considered classes of states is seen to have a Gaussian form, which is in accord with the prediction of other theoretical studies. The statistical fluctuations of the energy spectrum (the level spacing P(s) and the Dyson-Mehta (or statistics) are well described by the Gaussian orthogonal ensemble (GOE). Furthermore, these fluctuations are independent on the spin J.